The Effect of Transformational Leadership and Organizational Commitment on Employee Performance Through Turnover Intention - Dian Putri Utami; Sri Astuti Pratminingsih (Dinasti Review, 2026)
This study aims to analyze the effect of transformational leadership and organizational commitment on employee performance through turnover intention at PT Legrand Indonesia. The background of this study is based on the importance of leadership quality and employee commitment in improving performance and reducing employees’ intention to leave. This research employed a quantitative approach using a questionnaire with a Likert scale distributed to all 54 employees of PT Legrand Indonesia. The data were analyzed using descriptive and verification analysis. The results show that transformational leadership has a positive and significant effect on employee performance, while organizational commitment does not have a significant direct effect on employee performance. Turnover intention has a negative and significant effect on employee performance and fully mediates the effect of organizational commitment on employee performance, as well as partially mediates the effect of transformational leadership on employee performance. This study concludes that strengthening transformational leadership and organizational commitment by reducing turnover intention is essential for improving employee performance.